Effects of Kinesio Taping on Dynamic Knee Valgus Angle and Single Leg Hop in Badminton Players with Dynamic Knee Valgus - Karukunchit, Usa; Nimlek, Tanapat; Kumtaveewut, Kittapat (Journal of health and health management, 2025)
Dynamic knee valgus is an abnormal lower extremities movement during landing that may lead to knee injuries caused by insufficiency of core stability muscle. Kinesiotape can facilitate the core stability muscle. The objective of the study was to compare the effects of kinesiotaping muscle facilitation technique with 50% tension and the paper off with 10% tension group on rectus abdominis and erector spinae muscle on dynamic knee valgus and single leg jump in badminton players with dynamic knee valgus. A randomized controlled trial, double-blind was conducted on 34 badminton players with dynamic knee valgus aged between 18 and 25 years and weakness core muscles. Dynamic knee valgus angle and side hop test were collected at baseline and after taping. The two-way measures ANOVA was employed to analyze the data. The result demonstrated a statistically significant interaction effect between the taping tension groups and the time of taping on the knee valgus angle during movement (p < .05). However, no significant interaction effect was observed between the taping tension groups and the time of taping on the single-leg jump distance (p > .05). A comparison between the 50% and 10% kinesiotaping tension groups demonstrated statistically significant differences in dynamic knee valgus angle and single leg hop distance (p < .05). Kinesiotaping with 50% tension using a muscle facilitate technique reduces dynamic knee valgus angle and improves single-leg hop distance after being applied immediately and after 72 hours of taping in badminton players.